2019
DOI: 10.33373/anglo.v10i1.1892
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Listening Strategies Used by 4th Semester Students of Unrika and Their Listening Comprehension

Abstract: This study aimed to find out the most dominant listening strategies used by the students and to determine the correlation between the use of listening strategies and their listening comprehension. The type of the research was quantitative with correlational design. This study used a population of the 4th semester students of English Education Study Program, University of Riau Kepulauan, in which the sample was selected by total sampling technique. Data were collected by using listening strategy questionnaire a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
2
1
0
Order By: Relevance
“…From this, we can conclude that high performers try to plan, monitor, and evaluate. These results are consistent with those of Putri1 et al, (2019). They concluded that the highest percentage of listening strategies used by respondents were metacognitive strategies, reaching 74.1%.…”
Section: Discussionsupporting
confidence: 89%
“…From this, we can conclude that high performers try to plan, monitor, and evaluate. These results are consistent with those of Putri1 et al, (2019). They concluded that the highest percentage of listening strategies used by respondents were metacognitive strategies, reaching 74.1%.…”
Section: Discussionsupporting
confidence: 89%
“…The result of this study was quite different from previous studies which most of them revealed that there was significant relationship between the listening strategy and the listening performance. On the other hand, this present research had the same result as the one conducted by Putri and Dewi [18]. The samples of their study were 56 4 th semester students of English Education Study Program, University of Riau Kepulauan.…”
Section: Discussionsupporting
confidence: 51%
“…Many researchers have conducted studies on students' habits and academic achievement. Putri [12] researched the relationship between students' habits of listening to English songs and their listening skills, and the study results showed a significant correlation between students' habits of listening to English songs and students' listening skills. Nurjanah [13] also concludes, "The better students' habits in listening to songs, the better their listening skills."…”
Section: Introductionmentioning
confidence: 99%